Metode Evaluasi Program Kesehatan Ibu dan Anak di Kabupaten Sigi, Provinsi Sulawesi Tengah - Lexy Kareba; Saiful A; Parmi; Fitri Arni; Desak Susianawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Maternal and Child Health (KIA) program in Sigi Regency, Central Sulawesi Province, requires a comprehensive evaluation to ensure the effectiveness and sustainability of health interventions. This qualitative literature review aims to examine appropriate evaluation methods for the KIA program through an analysis of scientific literature. Literature was collected using keywords such as